PENGEMBANGAN BAHAN AJAR MATEMATIKA DENGAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN PRINSIP-PRINSIP MATEMATIKA DAN KEMAMPUAN PENALARAN LOGIS SISWA DI SMAN 1 JARAI KABUPATEN LAHAT - Astuti, Sondang (Program Studi Pendidikan Matematika FKIP Unlam Banjarmasin, 2017)
This study aims to produce teaching materials teaching math with discovery learning models that can improve understanding of the principles of mathematics and logical reasoning of students in SMA Negeri 1 Jarai district. Lahat. This type of research is the R & D (Research & Development), using the model of development of learning tools 4-D. Research subjects comprised for students of class X3 SMA Negeri 1 Jarai district. Lahat amounting to 23 people composed of 5 men and 18 women. Instruments in the study includes (1) sheet validation assessment of mathematics teaching materials discovery learning model (2) sheet practicality teaching materials discovery learning model, (3) copies of the effectiveness of teaching materials discovery learning model in the form of sheets of observations of the activities of teachers and students, a questionnaire sheet student responses, tests the ability of understanding the principles of mathematics, logical reasoning ability tests student, achievement test sheet. The collected data were analyzed with descriptive analysis. The results showed that the mathematical teaching materials discovery learning model developed included the category of very valid, practical, effective to improve understanding of the principles of mathematics and logical reasoning of students. Keywords: Instructional Materials Mathematics with Discovery Learning Model, the ability of understanding the principles ofmathematics, logical reasoning of students